A Brief Overview of Periodic Mesoporous Materials as Robust Supports for Photocatalytic Splitting of Water. (9th March 2015) - Peng, Rui; Mahoney, L J; Koodali, Ranjit T
Abstract : The growing demand to power the World has prompted intense research into the pursuit of developing sustainable and renewable sources that are carbon neutral. In this respect, the photocatalytic splitting of water to generate hydrogen and oxygen as fuel seems to be an attractive option. The rapid advances in the field of nanostructured materials has made it possible to design materials with novel properties, high reactivity, and catalytic efficiency. In recent years, mesoporous materials have proven to be popular choice for dispersion of photocatalytically active semiconductors. Their relatively high surface areas, large pore volumes, and tunable pore sizes allows for good dispersion of spatially isolated semiconductors. Such spatially isolated semiconductors and single-site containing mesoporous photocatalysts offer fresh perspective towards the realization of overall water splitting photocatalysts.